Steam Distillation of Citrus Waste Extract for Antimicrobial Metal Nanoparticle Synthesis - Javier Emanuel Castañeda-Aude; Enrique Díaz Barriga-Castro; Lizbeth Liliana Díaz-Muñoz; Javier Alberto Garza-Cervantes; José Rodríguez-Mirasol; José Rubén Morones-Ramírez; Héctor Javier Amézquita-García; David Alejandro De Haro-Del Río; Angel León-Buitimea; Noe Macias-Segura; Carlos Enrique Escárcega-González (Technologies)
This research presents a novel, sustainable, and eco-friendly method for the rapid green synthesis of nanoparticles with antibacterial properties. This method employs steam distillation to extract reducing and stabilizing agents from orange peel waste, followed by ultrasound-assisted synthesis. To the best of our knowledge, this is the first reported integration of these two techniques for nanoparticle production. The extracted materials were then subjected to rigorous characterization through a combination of analytical techniques, including FTIR, HPLC, and TEM. These analytical approaches enabled a comprehensive analysis of the synthesized NPs, revealing their size distribution within the range of 1.5 to 14 nm. Among the synthesized nanomaterials, AgNPs exhibited the most potent antibacterial activity, with statistically significant minimum inhibitory concentrations (MICs) of 16 ppm for E. coli ATCC and 32 ppm for resistant E. coli and E. faecalis strains. This study underscored the promise of valorizing citrus waste for nanomaterial synthesis and introduced a novel, scalable methodology for producing bioactive nanoparticles, promoting a more sustainable technology for this purpose. Notably, this research aligns with United Nations Sustainable Development Goal 12, which promotes responsible consumption and production by transforming organic waste into high-value functional nanomaterials for biomedical and environmental applications.